2005
DOI: 10.1038/sj.ejhg.5201521
|View full text |Cite
|
Sign up to set email alerts
|

Association of β2 adrenergic receptor polymorphisms and related haplotypes with triglyceride and LDL-cholesterol levels

Abstract: Adrenergic receptors regulate lipid mobilization, energy expenditure and glycogen breakdown. The b 2 adrenergic receptor (b 2 -AR) gene may constitute a potential candidate gene to explain part of the genetic predisposition to human obesity and correlated traits. With regard to the association between b 2 -AR gene polymorphisms and obesity-related metabolic disorders, published reports give conflicting results. We investigated the role of three polymorphisms, and related haplotypes of the b 2 -AR in the obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…22 Obese Spanish men with the Glu27Glu genotype had higher 2 hour post-load glucose concentrations compared with the Gln27Gln genotype. 23 Some studies also have found an association between the Gln allele and higher triglycerides concentrations, 25,26 while other investigators did not find an association between β2-AR and lipid levels. 27-29 …”
Section: Discussionmentioning
confidence: 99%
“…22 Obese Spanish men with the Glu27Glu genotype had higher 2 hour post-load glucose concentrations compared with the Gln27Gln genotype. 23 Some studies also have found an association between the Gln allele and higher triglycerides concentrations, 25,26 while other investigators did not find an association between β2-AR and lipid levels. 27-29 …”
Section: Discussionmentioning
confidence: 99%
“…Then the models were adjusted for such potential effect-mediators as systolic (SBP) and diastolic (DBP) blood pressures (mm Hg), smoking (ever smoked), diabetes, body-mass index (BMI; kg/m 2 ), total cholesterol (TC) and high-density lipoprotein (HDL) cholesterol (mg/100 ml) (Jalba et al, 2008; Petrone et al, 2006; Pinelli et al, 2006; Puddu et al, 2007). The absolute values of SBP, DBP, TC, and HDL were used in the regression models with increments of 10 mm Hg for SBP and DBP, and 10 mg/100 ml for TC and HDL cholesterol.…”
Section: Methodsmentioning
confidence: 99%
“…In a larger study of 642 overweight or obese subjects, ADRB2 Haplotype 1 predicted increased levels of triglycerides and LDL-cholesterol (the Thr164Ile polymorphism was not genotyped in this work). 89 The largest ADRB2 haplotype study to date involved genotyping of 523 patients who had myocardial infarction from a prospectively followed cohort of 14 916 initially healthy American men. Four controls (n ¼ 2092) were matched for each case and Haplotype 4 and the combined group of Haplotypes 1 and 3 had significantly altered risk of myocardial infarction with odds ratios of 0.178 (95% CI: 0.043-0.737; P ¼ 0.017) and 1.235 (95% CI: 1.031-1.480; P ¼ 0.022) respectively (the Cys-19Arg polymorphism was not genotyped in this work).…”
Section: Haplotype Approaches To Adrb1 and Adrb2mentioning
confidence: 99%